Preparing Teacher Candidates for Diverse Learners: Are We Doing Enough? - Spence, Melissa; Wesley, Tymika (Allies for Education, 2019)
Research on the academic achievement of K-12 students indicates that diverse students and students with exceptionalities face barriers to a quality education (Ladson-Billings, 2006). Responsibility falls to teacher preparation programs to ensure teacher candidates are prepared to engage diverse learners. We examine the literature regarding culturally responsive practices and teacher-efficacy in implementation. We further consider how a teacher preparation program assesses candidates’ ability to design instructional environments for diverse learners.